Pengaruh Rasio Lancar, Utang, dan Ekuitas Terhadap Harga Saham Dimoderasi ROA pada Perusahaan Makanan-Minuman BEI - Rizal Riyadi; Jan Horas Purba; Didit Pradipto; Muchammad Hamdani (LPPM Politeknik Pratama, 2026)
This study aims to analyze the effect of the Current Ratio (CR) and Debt-to-Equity Ratio (DER) on stock prices, with Return on Assets (ROA) acting as an intervening variable. The study employs panel data regression analysis using EViews 13 as the analytical tool. The results indicate that, in the first model, the Current Ratio (CR) has no effect and is not statistically significant on ROA, whereas the Debt-to-Equity Ratio (DER) has a positive and significant effect on ROA. In the second model, the findings reveal that CR does not have a significant effect on stock prices, and DER also does not significantly influence stock prices. However, ROA demonstrates a positive and significant effect on stock prices. Furthermore, the intervening analysis shows that CR does not significantly affect stock prices through ROA, while DER has a positive and significant indirect effect on stock prices through ROA.